A model-based graphical editor for supporting the creation, verification and validation of OntoUML conceptual models - Benevides, Alessander Bott (2010)
This thesis presents a model-based graphical editor for supporting the creation, verification and validation of conceptual models and domain ontologies in a philosophically and cognitively well-founded modeling language named OntoUML. The editor is designed in a way that, on one hand, it shields the user from the complexity of the ontological principles underlying this language. On the other hand, it reinforces these principles in the produced models by providing a mechanism for automatic formal constraint verification, hence ensuring that the created models will be syntactically correct. Assessing the quality of conceptual models is key to ensure that conceptual models can be used effectively as a basis for understanding, agreement and construction of information systems. For this reason, the editor is also capable of automatic generation of model instances by transforming these models into specifications in the logic-based language Alloy. As the generated Alloy specifications include the modal axioms of the foundational ontology underlyingOntoUML, named Unified Foundational Ontology (UFO), then the automatically generated instances will present modal behaviour while being dynamically classified, thereby supporting the validation of the modal meta-properties of the OntoUML types.